Winning ideas : lessons from free-market economics - Alkire, S (Oxford Poverty & Human Development Initiative (OPHI), 2007)
For economic ideas to take root and change history, a number of ingredients need to be present, ranging from individual agents to policy implementation. This paper identifies certain strategic levers that underlay the success of free market economists in promoting their approach in academia, society, and government. How did these economists move from a marginalized position where they could not publish or receive tenure and where their students were not hired at other leading universities, to a position of dominance? In particular, it examines the impact of F.A. Hayek, and of such institutions as the Mont Pelerin Society, the Institute for Economic Affairs (IEA) in Britain, and the funding arrangements. The paper draws on the wealth of secondary literature regarding the spread of free market economic ideas, particularly in the US, Latin America, and the UK, to identify five strategic activities and methods of transmission that were central to their advance, and will be relevant to others.